Green synthesis and characterization of nickel oxide (NiO) nanoparticles using barks of Muntingia calabura (Malayan Cherry) - Koh, Wei Fang (2024)
Nickel oxide nanoparticles (NiO NPs) were synthesized through a green synthesis pathway utilizing the aqueous bark extract of M. calabura with nickel(II) acetate tetrahydrate (Ni-A) and nickel(II) nitrate hexahydrate (Ni-N) serving as precursor salts. The presence of different anions in various nickel salts significantly impacts the nucleation and growth of NiO NPs by establishing unique formation environments which consequently modify the arrangement and surface characteristics of the faceted planes. The synthesized NiO NPs were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible (UV-Vis) Spectroscopy, X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-Ray Spectroscopy (EDX). In this study, NiO NPs were successfully synthesized using two different precursor salts, nickel(II) acetate tetrahydrate (Ni-A) and nickel(II) nitrate hexahydrate (Ni-N). The NiO NPs synthesized from Ni-A exhibited a maximum absorption peak at 346 nm with a corresponding band gap energy of 3.58 eV. FTIR analysis revealed a significant band at 479 cm⁻¹, attributed to NiO stretching vibrations that confirm the formation of NiO NPs. These NPs were spherical with particle sizes ranging from 44.7 - 65.6 nm, and displayed a trigonal (hexagonal axes) crystal structure with an average crystallite size of 18.53 nm. Similarly, the NiO NPs synthesized using Ni-N as the precursor salt showed a maximum absorption peak at 340 nm with a band gap energy of 3.64 eV. FTIR analysis indicated a band at 460 cm⁻¹ corresponding to NiO stretching vibrations which further validated the synthesis of NiO NPs. The resulting NiO NPs were also spherical with particle sizes ranging from 37.8 - 61.6 nm, and exhibited a cubic crystal structure with an average crystallite size of 27.22 nm. According to the EDX analysis, both NiO NPs synthesized utilizing Ni-A and Ni-N as precursor salts were free of contaminants and consisted solely of nickel and oxygen elements. These findings highlight the morphology and optical characteristics of NiO NPs will be modified depending on the precursor salt used.